Evaluation of three embolic agents in pig rete. - Lee, D H; Wriedt, C H; Kaufmann, J C; Pelz, D M; Fox, A J; Vinuela, F (American Journal of Neuroradiology, 1989)
In ongoing research into potential embolic agents, three substances were evaluated for their effectiveness in occluding the pig rete. Selective injection of these agents produced varying degrees of occlusion, with the most effective a microfibrillar collagen hemostat in a 33% ethanol solution. Angiostat, a collagen particulate, did not produce rete occlusion, and all pigs injected with it developed adverse effects, including coma and apnea. Tisseel, a tissue sealant, produced partial rete occlusion, but was uniformly difficult to manage through long catheters, and its use was discontinued. Microfibrillar collagen hemostat with ethanol appears to have the greatest potential as an embolic agent in low-flow structures.